A poética dos estranhos no videoclipe “Electric Guitar” a partir dos discursos videográficos de Lady Gaga - Pinto, Rafael Mendonça Lisita (2014)
This dissertation results of the research developed throughout the Master’s Degree course within the Art and Visual Culture Graduate Program in FAV-UFG. It aims to investigate de representation of uncanny identities in music videos, starting out with some analysis of Lady Gaga’s videos, in order to develop my videographic discourse in my music video “Electric Guitar”. The main goal is to continue creating subversive audiovisuals, which consist in primary and complex products that contemplate several parameters of approach, exploring sensorial matters and establishing bonds with historical, sociological and cultural issues. The first chapter presents Lady Gaga and her artistic body of work which, curiously, defends minorities in spite of the singer being inserted into the star system. The second chapter introduces concept of “the uncanny”, from teoretical dialogues and, also, addresses their presence in music videos. The third chapter focuses on the study of music video as a audiovusal format, its relevance in visual culture and how they develop through media. The forth chapter reapproaches Lady Gaga’s music videos, selected according to this investigation theme, focusing on their analysis. The last chapter discusses the creative experience of “Electric Guitar” through my goal of reassuring the relevance of studying the uncanny and, also, my attempt to expand music video’s frontiers by employing new perspectives to them, without escaping the plastic aesthetics predominant in pop.